Risk and financial management : mathematical and computational methods - Tapiero, Charles S. (Chichester, West Sussex ; Hoboken, NJ : John Wiley, 2004)
The book is ideally suited to both students of mathematical finance with little background in economics and finance, and students of financial risk management, as well as finance practitioners requiring a clearer understanding of the mathematical and computational methods they use every day. It combines the required level of rigor to support the theoretical developments, with a practical flavour through many examples and applications.
Includes bibliographical references and index.
rpm 31/05/13
Loans
Keywords: Risk management; Finance - mathematical models; Financial management